2015
DOI: 10.13102/sociobiology.v62i3.732
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Resistance and Feeding Preference of 24 Wood Species to Attack by Heterotermes indicola (Wasmann) and Coptotermes heimi (Isoptera: Rhinotermitidae, Termitidae) in Pakistan.

Abstract: Present study was conducted to evaluate the laboratory and field preference of 24 Pakistani wood species: Azadirachta indica (Neem), Pinus  roxberghii (Chir), Dalbergia sissoo (Sheesham), Populus deltoides (Popular), Albizzia lebbeck (Shirin), Abies pindrow(fir), Alstonia scholaris (Alstonia), Erythrina suberosa (Gul-e-nister), Eucalyptus citriodora (safaeda), Ficus religiosa (Bohar), Heterophragma adenophyllum (Beeri Patta), Melia azedarach (Derek), Pinus wallichiana (Chir), Terminalia arjuna (Arjun), Acacia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Weight loss of boiled Z. mauritiana was significantly higher compared to fresh + boiled + fresh Z. mauritiana 1.65%, boiled + fresh + boiled Z. mauritiana 5.12%, fresh+ boiled Z. mauritiana 4.53%, fresh Z. mauritiana 3.31% respectively. Dugal and Latif (2015) reported another species Z. jujuba resistant to Coptotermes heimi and Heterotermes indicola along with several other trees including Mangifera indica, Erythrina suberosa, Betula utilis, Elaeis guineensis, Ficus religiosa, Heterophragma adenophyllum, Terminalia arjuna, Moringa oleifera, Putranjiva roxburghii, and Syzygium cumini.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss of boiled Z. mauritiana was significantly higher compared to fresh + boiled + fresh Z. mauritiana 1.65%, boiled + fresh + boiled Z. mauritiana 5.12%, fresh+ boiled Z. mauritiana 4.53%, fresh Z. mauritiana 3.31% respectively. Dugal and Latif (2015) reported another species Z. jujuba resistant to Coptotermes heimi and Heterotermes indicola along with several other trees including Mangifera indica, Erythrina suberosa, Betula utilis, Elaeis guineensis, Ficus religiosa, Heterophragma adenophyllum, Terminalia arjuna, Moringa oleifera, Putranjiva roxburghii, and Syzygium cumini.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative susceptibility/resistance tests of woods against H. indicola have indicated that Dalbergia sissoo, Azadirachta indica, Syzygium cumini and Pinus roxburghii, were resistant while Populus euramericana, Bauhinia variegate, Mangifera indica and Populus deltoides were ranked as susceptible to termite attack (Dugal andLatif 2015, Afzal et al 2017). The nature of resistance of some heartwoods to termite attack is mostly attributed to toxic compounds sequestered by the living tree within the heartwood (Kirker et al 2013, Hassan et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Wood type and size affect conspecific interactions and production of secondary reproductives of drywood termites (Evans et al, 2011;Korb, 2006), as do wood anatomy and volatile emissions (Himmi et al, 2016;Scheffrahn & Rust, 1983;Xu, Feng, Zhong, Zheng, & Chen, 2015). Curiously, resistance of tropical wood and its underlying causes were seldom investigated and the studies carried out so far focus on recognizing preferences and mainly by subterranean termite species with few exceptions (Cornelius & Osbrink, 2015;Lee, Bardunias, Su, & Yang, 2008;Lee & Forschler, 2016;Manzoor, Abbas, & Latif, 2015;Oberst, Lai, & Evans, 2018;Rust & Reierson, 1977;Rust & Su, 2012;Scheffrahn & Rust, 1983). Nonetheless, varied resistance to the West Indian drywood termite exists (Cosme, Haro, Guedes, Della Lucia, & Guedes, 2018;Gonçalves & Oliveira, 2006;Oliveira, Paes, & Vidaurre, 2017), and the wood physical properties, namely hardness and specially density, are important determinants of colonization and wood consumption by this invasive pest species (Cosme et al, 2018).…”
mentioning
confidence: 99%